Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Customer Warung Kopi 88 - Andi Tan; Wasiman Wasiman (SEIKO : Journal of Management & Business, 2022)
Over time, Batam City can be known as one of the culinary cities in Indonesia. This opportunity makes entrepreneurs have to work hard in understanding all the needs of their consumers so that it can provide benefits for entrepreneurs to plan marketing strategies to provide satisfaction for consumers. Consumer satisfaction is a consumer feeling that is closely related to the use of certain goods or services. When compared to expected performance or results, this emotional response can manifest as feelings of pleasure or disappointment. Customers will not be happy if the goods or services used are substandard and not as expected. However, consumers will be satisfied if the goods or services they receive are in accordance with their expectations. Service standards and advertising are existing aspects that can contribute to client happiness. The sampling technique uses saturated samples. For data collection purposes, the researcher distributed questionnaires, which contained a list of questions that had to be answered by the participants. The method used in the findings contained in this study is a quantitative-based research by conducting multiple linear analysis. The results of research based on a study will certainly be able to prove that Service Quality and Promotion have a significant effect on customer satisfaction at Warung Kopi 88. Keywords: Customer Satisfaction; Promotion; Service Quality.